Exercise and Fitness Neuroprotective Effects: Molecular, Brain Volume and Psychological Correlates and Their Mediating Role in Healthy Late-Middle-Aged Women and Men - Castells-Sánchez, Alba; Roig-Coll, Francesca; Dacosta-Aguayo, Rosalia; Lamonja-Vicente, Noemí; Sawicka, Angelika K.; Torán-Monserrat, Pere; Pera, Guillem; Montero-Alía, Pilar; Heras-Tebar, Antonio; Domènech, Sira; Via, Marc; Erickson, Kirk I.; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Although exercise is known to have a neuroprotective effect in aging, the mediators underlying the exercise-cognition association remain poorly understood. In this paper we aimed to study the molecular, brain and behavioral changes related to physical activity and their potential role as mediators. Methods: We obtained demographic, physical activity outcomes (sportive physical activity and cardiorespiratory fitness (CRF)), plasma biomarkers (TNF-α, ICAM, HGF, SDF1-α and BDNF), structural-MRI (brain volume areas), psychological and sleep health (mood, depressive and distress symptoms and sleep quality) and multi-domain cognitive data from 115 adults aged 50-70 years. We conducted linear regression models and mediation analyses stratifying results by sex in a final sample of 104 individuals (65 women (age=56.75 ± 4.96) and 39 men (age=58.59 ± 5.86)). Results: Women engaging in greater amounts of exercising showed lower TNF-α levels and greater dorsolateral prefrontal cortex and temporal lobe volumes. Men engaging in greater amounts of exercise showed greater temporal lobe volumes. CRF levels were not related to any of the analyzed outcomes in women but in men higher CRF was associated with lower TNF-α, HGF and ventricle volumes, greater volume of temporal and parietal lobes and fewer depressive symptoms and better mood. In men, reduced TNF-α and HGF levels mediated brain and cognitive CRF-related benefits. Conclusion: Our results show that exercise is a promising approach for influencing inflammation and brain volume and also contributes to ongoing discussions about the physiological mediators for the association between CRF and cognition in men.